Development of soft inchworm robot with friction control of feet using double-network gel. (19th March 2023) - Selvamuthu, Moses Gladson; Tadakuma, Riichiro; Fujiwara, Naofumi; Yoshida, Kazunari; Takagi, Minoru; Hoshino, Hiroyuki; Suzuri, Yoshiyuki; Furukawa, Hidemitsu
Abstract : In this study, we investigate the development of an inchworm-inspired soft robot with active friction control of its feet. The focus is on its design, modeling, and locomotion principle. Friction control is achieved dynamically by using a unique material called double-network hydrogel (DN gel) to form the legs of the inchworm robot. DN gels are soft but tough materials, and they exhibit the unique characteristic of frictional difference on the surface under an applied voltage. This property is exploited to realize locomotion. A wide range of robot speeds can be realized through appropriate control of the voltage applied to its legs. Motion strategies with simultaneous control of actuation force and leg friction allow for greater flexibility in locomotion. The behavior of inchworm locomotion with change in the frictional difference between legs and actuator force was predicted using the developed mathematical model and was confirmed through experiments. Three different inchworm robot prototypes were developed and studied. The inchworm robot is characterized by low cost and inherent compliance, and it is easily disposable. GRAPHICAL ABSTRACT: UF0001